2015
DOI: 10.1007/s11605-015-2747-x
|View full text |Cite
|
Sign up to set email alerts
|

Early Cholecystectomy Is Superior to Delayed Cholecystectomy for Acute Cholecystitis: a Meta-analysis

Abstract: Early laparoscopic cholecystectomy in acute cholecystitis demonstrated decreased incidence of wound infections, a shorter total length of stay and decreased costs with no difference in the rates of mortality, bile duct injuries, bile leaks and conversions. These results support that early laparoscopic cholecystectomy is the best care and should be considered a routine in patients presenting with acute cholecystitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
84
3
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 48 publications
8
84
3
1
Order By: Relevance
“…[12][13][14] Recent meta-analyses concluded that early laparoscopic cholecystectomy appears to be safe and reduces total hospital stay. [15][16][17] Similar conclusions were also reached in a current Cochrane systemic review. 18 A recent multicenter (n = 35 centers) randomized trial (n = 618 patients), studying early versus delayed cholecystectomy, finally settled the issue showing that laparoscopic cholecystectomy, when performed within 24 h of hospital admission, was significantly better as compared to conservative treatment regarding both morbidity and costs.…”
Section: Introductionsupporting
confidence: 82%
“…[12][13][14] Recent meta-analyses concluded that early laparoscopic cholecystectomy appears to be safe and reduces total hospital stay. [15][16][17] Similar conclusions were also reached in a current Cochrane systemic review. 18 A recent multicenter (n = 35 centers) randomized trial (n = 618 patients), studying early versus delayed cholecystectomy, finally settled the issue showing that laparoscopic cholecystectomy, when performed within 24 h of hospital admission, was significantly better as compared to conservative treatment regarding both morbidity and costs.…”
Section: Introductionsupporting
confidence: 82%
“…These rates are higher than reported for non-elderly patients undergoing emergency cholecystectomy for acute cholecystitis, which has been extensively investigated in previous studies, being approximately 15 and <1%, respectively [25] . Yet, 4 of the 5 included studies comparing perioperative outcomes of early cholecystectomy in elderly and younger patients showed no significant difference in terms of perioperative morbidity or mortality [17][18][19]21] .…”
Section: Discussionmentioning
confidence: 56%
“…Studies focusing on non-elderly patients undergoing early cholecystectomy for acute cholecystitis demonstrated a conversion rate from laparoscopic to OC of 13% [25] . The present study showed a conversion rate of 23%.…”
Section: Discussionmentioning
confidence: 99%
“…With the results of recent randomized controlled trials (RCT) and meta-analyses of RCT, it has been accepted that patients undergoing early LC have significantly shorter total length of hospital stay compared with delayed LC [12]. Other clinical outcomes including mortality, complication rates and conversions to open procedure appear to favour early LC, but were not statistically significant.…”
Section: Introductionmentioning
confidence: 99%